Adaptasi Terhadap Perubahan Iklim dan Dinamika Kebijakan: Strategi Pengelolaan Sumber Daya Air di Kabupaten Merauke - Pakidi, Chalvyn Silasa; Tambaip, Beatus (Jurnal Ilmu Sosial dan Humaniora, 2025)
Climate change and public policy dynamics pose significant challenges to water resources management, especially in marginal tropical areas such as Merauke Regency. This study examines adaptation strategies for community-based water resources management by integrating local wisdom, ecosystem approaches, and responsive and participatory policies. The research method uses a qualitative approach with data collection through in-depth interviews, field observations, and policy document analysis. The results show that effective adaptation requires synergy between stakeholders and strengthening of local institutions to increase socio-ecological resilience to climate change. The resulting strategy framework can be a model for sustainable and applicable adaptation in areas with similar geographic and social conditions. This study makes an important contribution to the development of responsive and inclusive climate change adaptation policies